Topological Krasner hyperrings with special emphasis on isomorphism theorems - Manooranjan Singha; Kousik Das (Applied General Topology, 2022)
Krasner hyperring is one of the generalizations of the classical ring in literature. In this paper, the notion of topological Krasner hyperring is introduced as a generalization of topological ring and variant of isomorphism theorems are studied